2014
DOI: 10.1007/s00417-014-2886-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of intravitreal bevacizumab vs. ranibizumab for myopic CNV

Abstract: Myopic CNV equally benefits from on-demand intravitreal injection of either bevacizumab or ranibizumab; the therapeutic effect is independent of previous PDT and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
2
13
0
2
Order By: Relevance
“…Despite these limitations, our study supports the current data available regarding the long-term effectiveness of anti-VEGF therapies in patients with mCNV. Several studies on the treatment of mCNV with ranibizumab report good visual outcomes over more than 12 months of follow-up, 18 , 20 – 26 , 29 , 30 but most follow preestablished treatment protocols. A Portuguese case series on 39 eyes reported a mean BCVA gain of 8.0 ETDRS letters after 3 years of follow-up with 35% of patients gaining ≥15 letters after this time period.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, our study supports the current data available regarding the long-term effectiveness of anti-VEGF therapies in patients with mCNV. Several studies on the treatment of mCNV with ranibizumab report good visual outcomes over more than 12 months of follow-up, 18 , 20 – 26 , 29 , 30 but most follow preestablished treatment protocols. A Portuguese case series on 39 eyes reported a mean BCVA gain of 8.0 ETDRS letters after 3 years of follow-up with 35% of patients gaining ≥15 letters after this time period.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, NV in eyes with concomitant AMD and HM showed a different clinical course and response to treatment compared to NV associated with typical AMD, as previously reported in the literature. 33,34 In our population, more anti-VEGF intravitreal injections were needed to restore functional and anatomic parameters than that reported in the purely myopic population [35][36][37][38] (3.8 injections in our AMD/myopia population versus 1.8-3.6 injections in the purely myopic population using a PRN protocol in the first year of treatment). [28][29][30][31] However, 3.8 represents a reduced number of injections needed to optimally treat NV in AMD (4.3-6.9 injections in the first year of PRN treatment has been reported).…”
Section: Discussionmentioning
confidence: 78%
“…Similar data were found in the study by Cohen et al [25] with a mean intravitreal ranibizumab number of 3.5 (range 1–12) over a mean follow-up of 39.3 months. Pece et al [38] reported 2.3 intravitreal injections in the ranibizu­mab subgroup during 20-month follow-up; similarly, Iacono et al [16] reported a mean of 2.5 intravitreal rani­bizumab injections over 18 months. A 6-year analysis by Ruiz-Moreno et al [22] revealed a mean of 3.3 injections, and in the longest study of ranibizumab monotherapy for mCNV, Hefner and Gerding [31] performed a mean of 3.5 injections (range 1–12) during a mean follow-up of 85 months.…”
Section: Discussionmentioning
confidence: 99%